Bright and two-photon active red fluorescent dyes that selectively move back and forth between the mitochondria and nucleus upon changing the mitochondrial membrane potential. Issue 45 (6th November 2018) - Seki, Hitomi; Onishi, Shozo; Asamura, Naoya; Suzuki, Yasutaka; Kawamata, Jun; Kaneno, Daisuke; Hadano, Shingo; Watanabe, Shigeru; Niko, Yosuke
Abstract : Pyrene-based two-photon active and bright red emitters that localize between the mitochondria and nucleus in response to changes in the mitochondrial membrane potential. Abstract : Since mitochondrial dysfunction was discovered to be the underlying cause of several severe diseases, fluorescent probes with excellent optical properties for visualising and monitoring the mitochondrial membrane potential (MMP) (a parameter of mitochondrial vitality) have been in high demand. Herein, we present novel pyrene-based dyes exhibiting remarkably large two-photon absorption around 900 nm and bright red emission around 620 nm (two-photon brightness ( Φσ 2 ) = 425–525 GM), with selective localisation to the mitochondria or nucleus in response to changes in the MMP, providing several advantages over traditional MMP-monitoring probes such as Rhodamine 123 ( Φσ 2 = 64 GM). The intracellular behavior of the new dyes was investigated in detail. The driving forces for the dyes to dissociate from the mitochondria and migrate toward the nucleus upon decreasing the MMP were two key molecular characteristics: the dyes' permeability to mitochondrial membranes and their affinity to nuclear DNA. The results provide significant insights into improving the molecular design of the dyes.